2020
DOI: 10.1109/jmems.2020.2967174
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Lithography Fabrication of SU-8 Polymer Structures for Cell Studies

Abstract: Flat surfaces decorated with micro-and nanostructures are important tools in biomedical research used to control cellular shape, in studies of mechanotransduction, membrane mechanics, cell migration and cellular interactions with nanostructured surfaces. Existing methods to fabricate surface-bound nanostructures are typically limited either by resolution, aspect ratio or throughput. In this work, we explore electron beam lithography based structuring of the epoxy resist SU-8 on glass substrate. We focus on a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Using previously established protocols, we have fabricated glass cover-slips decorated with precisely defined arrays of vertically oriented SU-8 nanopillars (NP) with variable separation and defined geometry[63]. These surfaces with NP densities of 456, 205, 115 and 29 NPs/100 μm 2 (corresponding to pitches of 500 nm, 750 nm, 1000 nm and 2000 nm) were used to investigate the nanostructure induced changes to morphology, distribution of focal adhesions (FAs) and actin cytoskeleton structure of U2OS cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using previously established protocols, we have fabricated glass cover-slips decorated with precisely defined arrays of vertically oriented SU-8 nanopillars (NP) with variable separation and defined geometry[63]. These surfaces with NP densities of 456, 205, 115 and 29 NPs/100 μm 2 (corresponding to pitches of 500 nm, 750 nm, 1000 nm and 2000 nm) were used to investigate the nanostructure induced changes to morphology, distribution of focal adhesions (FAs) and actin cytoskeleton structure of U2OS cells.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work we have described detailed protocols for fabrication of SU-8 polymer nanostructures on flat glass surfaces [63], and explored cell behaviour for two different cell lines on these surfaces [48,45]. In this work, we use electron beam lithography (EBL) to fabricate surfaces decorated with vertically aligned SU-8 polymer structures to study changes in actin cytoskeletal and FA organisation in the osteosarcoma epithelial cell line U2OS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EBL can be used to build 3D micro- or nanostructures that can become tools for modifying the cellular shape or for controlling cell migration [ 2 ]. Vinje et al have carefully established control over the spatial resolution and fabrication process within films of SU-8 polymer-based resist and have obtained arrays of high-aspect ratio lines and pillars with a horizontal periodicity of ~100 nm [ 2 ]. Other more complex polymeric patterns for biological purposes can be sculptured by EBL [ 17 ].…”
Section: Top–down Lithographic Methodologiesmentioning
confidence: 99%
“…In the past years, a variety of conventional [ 1 , 2 , 3 , 4 ] and less conventional [ 5 , 6 , 7 ] micro- and nano-patterning methods have been used to generate periodic surface relief patterns. As a consequence, a huge diversity of patterned materials developed in time.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of thin films less than 10 μm have been investigated by Vinje et al [31]. They found that even in the case of thin films, the relationship between the film thickness and the spin coating speed has several variations.…”
Section: Introductionmentioning
confidence: 99%